Pollen-based vegetation record from IODP Site 353-U1446 (Bay of Bengal), Marine Isotope Stage 11 - Dulce Oliveira; Stéphanie Desprat; Qiuzhen Yin; Coralie Zorzi; Zhipeng Wu; Krishnamurthy Anupama; Srinivasan Prasad; Montserrat Alonso-Garcia; Philippe Martinez (PANGAEA, 2025)
Pollen-based vegetation reconstruction from IODP Expedition 353 Site U1446 (19°5 extquotesingleN, 85°4 extquotesingleE, 1430 m water depth) from 437,000 to 363,000 years ago, a period centered on MIS 11. The dataset includes counts and percentages of all identified pollen and spore morphotypes, as well as the main ecological groups: tropical forest, wet evergreen forest, tropical deciduous forest and xerophyte plants. Pollen analysis: Samples of 1–5 g of dry sediment were processed using the standard protocol for marine samples, which includes coarse sieving (150 μm mesh), consecutive treatments with cold HCl and cold HF and micro-sieving (5 μm mesh). Residues were mounted unstained in a mobile media (glycerol) to allow polar and equatorial observations of pollen grains. Counting was performed using a Nikon light microscope at exttimes500 and exttimes1000 (oil immersion) magnification.